A phage display-based strategy for the de novo creation of disulfide-constrained and isomer-free bicyclic peptide affinity reagents. Issue 32 (5th April 2018) - Zha, Mirao; Lin, Ping; Yao, Hongwei; Zhao, Yibing; Wu, Chuanliu
Abstract : We report a phage-screening strategy for the development of bicyclic peptide ligands constrained with two sterically different and isomerically forbidden noncanonical disulfide bridges without elaborate chemical modifications and recourses to genetic code reprogramming. Abstract : Bicyclic peptides have been attractive scaffolds for developing high affinity reagents for biomacromolecules. Here we report a general phage-screening strategy for the development of bicyclic peptide ligands constrained with isomerically-forbidden disulfide bridges without elaborate chemical modifications and recourses to genetic code reprogramming.